Endometrioid Carcinoma Metastasis and Minute Pulmonary Meningothelial-Like Nodules in the Lung: A Case Report - Konur, Müberra; Belen Aydoğmuş, Burcu; Özdemir, Çiğdem (The European Research Journal, 2026)
Minute pulmonary meningothelial-like nodules (MPMN) are rare pulmonary lesions characterized by the proliferation of cells showing meningothelial differentiation and are most commonly detected incidentally. Their coexistence with pulmonary metastases is uncommon. We report a case of metastatic endometrioid carcinoma of the lung associated with incidentally identified MPMN. A 60-year-old woman with a history of endometrioid carcinoma presented with a soft tissue density lesion measuring 38×42 mm with ill-defined margins, causing mild narrowing of the right upper lobe bronchus on computed tomography. Surgical resection of the lung mass was performed. Intraoperative frozen section examination revealed a malignant epithelial neoplasm consistent with adenocarcinoma. On permanent sections, histopathological evaluation demonstrated an epithelial tumor composed of complex and cribriform glandular structures within a desmoplastic stroma, accompanied by loss of polarity and nuclear enlargement, consistent with metastatic endometrioid carcinoma. In the wedge resection specimen obtained after frozen section examination, multiple microscopic lesions were identified in the non-neoplastic lung parenchyma. These lesions consisted of bland cells with round to ovoid nuclei arranged in whorled patterns along the alveolar septa. Immunohistochemical analysis supported the diagnoses of metastatic endometrioid carcinoma and MPMN, respectively. Based on the histopathological, immunohistochemical, and clinical findings, the mass lesion was diagnosed as metastatic endometrioid carcinoma, while the incidental parenchymal lesions were diagnosed as MPMN. To our knowledge, coexistence of MPMN with metastatic endometrioid carcinoma is exceedingly rare and not well documented in the indexed English-language literature.